Prognostic impact of dose reduction in androgen receptor pathway inhibitors for castration-resistant prostate cancer - Shigetomo Yamada; Masaki Shiota; Leandro Blas; Takashi Matsumoto; Eiji Kashiwagi; Ario Takeuchi; Junichi Inokuchi; Ken-ichiro Shiga; Akira Yokomizo; Masatoshi Eto (Prostate International, 2022)
Background: Androgen receptor pathway inhibitors (ARPIs) such as abiraterone and enzalutamide have been shown to prolong survival in patients with advanced prostate cancer. However, there is limited evidence on the anticancer effect of a reduced dose of ARPIs. This study compared the prognosis in patients with chemotherapy-naïve castration-resistant prostate cancer (CRPC) between ARPI treatment with standard dose and treatment with reduced dose. Methods: Japanese patients who were treated with ARPI as first-line treatment for CRPC between 2014 and 2018 were included. The associations between dose reduction and clinicopathological factors, progression-free survival, and overall survival were investigated. Results: Of the 162 patients included, 33 (20.4%) patients had their dose reduced during ARPI treatment. In the multivariate analysis, higher PSA, abiraterone treatment, and dose reduction were significant prognostic factors for progression-free survival (PFS); however, dose reduction was not associated with overall survival. In the enzalutamide-treated group, the median PFS was 12.1 months (95% CI, 8.5–21.4 months) in the standard-dose group and 7.2 months (95% CI, 5.0–11.5 months) in the reduced-dose group (P = 0.038). Conclusion: This study suggests inferior oncological outcome when treated with reduced-dose ARPI for CRPC. Full-dose administration of ARPI for CRPC may be appropriate if feasible.